2019
DOI: 10.1126/science.aay1186
|View full text |Cite
|
Sign up to set email alerts
|

A cortical-brainstem circuit predicts and governs compulsive alcohol drinking

Abstract: What individual differences in neural activity predict the future escalation of alcohol drinking from casual to compulsive? The neurobiological mechanisms that gate the transition from moderate to compulsive drinking remain poorly understood. We longitudinally tracked the development of compulsive drinking across a binge-drinking experience in male mice. Binge drinking unmasked individual differences, revealing latent traits in alcohol consumption and compulsive drinking despite equal prior exposure to alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
179
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 48 publications
18
179
1
Order By: Relevance
“…Compulsive sucrose-seeking is relatively understudied, while many more previous studies have examined compulsive drug-seeking. Large individual variability in compulsivity has been observed in animals working for drugs such as cocaine and alcohol (Giuliano et al, 2019;Siciliano et al, 2019). Consistent with those findings, we also found large individual differences in compulsivity.…”
Section: Discussionsupporting
confidence: 92%
“…Compulsive sucrose-seeking is relatively understudied, while many more previous studies have examined compulsive drug-seeking. Large individual variability in compulsivity has been observed in animals working for drugs such as cocaine and alcohol (Giuliano et al, 2019;Siciliano et al, 2019). Consistent with those findings, we also found large individual differences in compulsivity.…”
Section: Discussionsupporting
confidence: 92%
“…These resistant rats displayed behaviours that have been suggested to be the operationalisation in rodents of two features that characterise AUD, namely compulsive drinking behaviour and decreased interest for reinforcers other than the drug itself [25][26][27] . In line with previous studies 26,34,40 , the development of compulsive drinking behaviour in vulnerable animals was shown not to be predicted by the individual tendency to drink high levels of alcohol, thereby confirming that the development of this behavioural feature of alcohol addiction is not simply related to the magnitude of pharmacological exposure to alcohol. This dissociation, which challenges a drug-centred view of drug addiction and further emphasising the importance of factors of vulnerability 41,42 , is not restricted to alcohol.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, others have demonstrated that reductions in neural activity of dmPFC projections to the brainstem could induce compulsive alcohol drinking behavior in mice, supporting the idea that disengagement of the dmPFC contributes to compulsive action 55 .…”
Section: Discussionmentioning
confidence: 80%